2020
DOI: 10.3390/ijerph17155417
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental Social Media Publications on User Satisfaction with and Trust in Tourism Businesses

Abstract: The main aim of the present study was to analyze whether publications related to environmental sustainability in social media directly and positively influence user satisfaction with and trust in tourism businesses. Our second goal was to determine whether the influence of environmental sustainability and satisfaction is moderated by users’ gender. Data collection was performed using a questionnaire. The questionnaire responses were analyzed using the partial least squares-structural equation modeling (PLS-SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…The trust of the consumer has become an imperative component that calls for attention in mobile commerce (Hong and Cha, 2013;Shaw, 2014) and also in tourism businesses (Martínez-Naval on et al, 2020). Additionally, if the consumers trust the goodwill of the merchant, they will have an intention to purchase from them (Han and Windsor, 2011;Hajli, 2014).…”
Section: Trustmentioning
confidence: 99%
“…The trust of the consumer has become an imperative component that calls for attention in mobile commerce (Hong and Cha, 2013;Shaw, 2014) and also in tourism businesses (Martínez-Naval on et al, 2020). Additionally, if the consumers trust the goodwill of the merchant, they will have an intention to purchase from them (Han and Windsor, 2011;Hajli, 2014).…”
Section: Trustmentioning
confidence: 99%
“…Furthermore, the current study confirmed a significant positive effect of tourist trust on satisfaction, which is consistent with the findings of Wu et al (2016) and Amoako et al (2019) . Interestingly, the relationship between tourist trust and satisfaction has been in academic controversy, with some scholars arguing that satisfaction affects tourist trust ( Song et al, 2014 ; Al-Ansi and Han, 2019 ; Martinez-Navalon et al, 2020 ). However, in this context, tourist trust affects satisfaction, which can be explained by the fact that tourism public health services are closer to the basic needs of tourists, such as health and safety.…”
Section: Impact Of Tphsq On Tourist Loyaltymentioning
confidence: 99%
“…Previous studies show that various functions of tourism mobile apps, such as mobile travel guides, recommendation systems, location-based services, and directions, are suitable to satisfy the needs of tourism consumers [11,12]. As a result, mobile apps are being used as a marketing tool to attract consumers in the tourism industry [13,14]. In addition, mobile apps increase consumers' negative perceptions, such as privacy and security concerns [15].…”
Section: Theoretical Background 21 Technology Readinessmentioning
confidence: 99%